Iatrogenic IVC Perforation after Successful Catheter-Directed Thrombolysis - Ata Firoozi; Jamal Moosavi; Omid Shafe; Parham Sadeghipour (Case Reports in Vascular Medicine)
Central vein perforation as a rare complication of venous interventions is considered a nightmare if occurring in thoracic cage but behaves benignly in abdominal or pelvic region. This is not a rule, as we unfortunately encountered during the procedure of venous intervention in our patient. Although mechanical control of iatrogenic perforation or rupture is the first and most critical step during interventional procedures, the importance of anticoagulant and thrombolytic agents reversal should not be overlooked.